1998
DOI: 10.2105/ajph.88.11.1699
|View full text |Cite
|
Sign up to set email alerts
|

Physician financial incentives and feedback: failure to increase cancer screening in Medicaid managed care.

Abstract: OBJECTIVES: A randomized controlled trial evaluated the impact of feedback and financial incentives on physician compliance with cancer screening guidelines for women 50 years of age and older in a Medicaid health maintenance organization (HMO). METHODS: Half of 52 primary care sites received the intervention, which included written feedback and a financial bonus. Mammography, breast exam, colorectal screening, and Pap testing compliance rates were evaluated. RESULTS: From 1993 to 1995, screening rates doubled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 23 publications
1
153
0
Order By: Relevance
“…Three studies (Grady et al 1997;Hillman et al 1998;Hillman et al 1999) didn't detect any significant effect of P4P bonus rewards or bonus rewards combined with performance feedback on physician compliance with cancer screening, pediatric immunization and mammography referrals. Two studies (Fairbrother et al 1999;Fairbrother et al 2001) found that a bonus or bonus with performance feedback incentives increased documented coverage levels for childhood immunization, but the measured increase 6 was primarily due to better documentation not better immunization practices.…”
Section: Empirical Evidence On Physician Response To P4pmentioning
confidence: 97%
“…Three studies (Grady et al 1997;Hillman et al 1998;Hillman et al 1999) didn't detect any significant effect of P4P bonus rewards or bonus rewards combined with performance feedback on physician compliance with cancer screening, pediatric immunization and mammography referrals. Two studies (Fairbrother et al 1999;Fairbrother et al 2001) found that a bonus or bonus with performance feedback incentives increased documented coverage levels for childhood immunization, but the measured increase 6 was primarily due to better documentation not better immunization practices.…”
Section: Empirical Evidence On Physician Response To P4pmentioning
confidence: 97%
“…One P4P study in primary care setting was not successful at reaching targets. The reason was that physicians participated in many plans, so the bonus for healthcare management alternatives members alone may not have had the necessary impact on physicians' overall income [56]. In some P4P systems, physicians are rewarded for high delivery of care with no punishment, whereas other programs put the physician in risk with not paying until the physician achieves the predefined target [57].…”
Section: Discussionmentioning
confidence: 99%
“…Pay-forperformance had the greatest effect on low rather than high performers [3,9,16,33,44,64,72]. Approaches with purely positive incentives (versus winners and losers) [12,16,34,35,48] and paying clinicians rather than hospitals were more effective [16,61]. Pay-for-performance focused on the individual provider found no relationship between frequency [17] and size of incentive on effect sizes [72].…”
Section: Search Strategies and Criteriamentioning
confidence: 93%
“…The answer to the first question was, in most cases, a qualified yes; only three studies [34,35,65] did not report improvement. However, the overall effect was small and highly context-specific [16,28,49,61,66,67,72].…”
Section: Search Strategies and Criteriamentioning
confidence: 98%